Markers of tumor-associated macrophages and microglia exhibit high intratumoral heterogeneity in human glioblastoma tissue - Ispirjan, Mikael; Marx, Sascha; Freund, Eric; Fleck, Steffen K.; Baldauf, Joerg; Roessler, Karl; Schroeder, Henry W.S.; Bekeschus, Sander (OncoImmunology, 2024)
Human glioblastoma multiforme (GBM) is a highly aggressive tumor with insufficient therapies available. Especially, novel concepts of immune therapies fail due to a complex immunosuppressive microenvironment, high mutational rates, and inter-patient variations. The intratumoral heterogeneity is currently not sufficiently investigated. Biopsies from six different locations were taken in a cohort of 16 GBM patients who underwent surgery. The tissue slides were analyzed utilizing high-content imaging microscopy and algorithm-based image quantification. Several immune markers for macrophage and microglia subpopulations were investigated. Flow cytometry was used to validate key results. Besides the surface marker, cytokines were measured and categorized based on their heterogenicity and overall expression. M2-like antigens, including CD204, CD163, Arg1, and CSF1R, showed comparatively higher expression, with GFAP displaying the least intratumoral heterogeneity. In contrast, anti-tumor-macrophage-like antigens, such as PSGL-1, CD16, CD68, and MHC-II, exhibited low overall expression and concurrent high intratumoral heterogeneity. CD16 and PSGL-1 were the most heterogeneous antigens. High expression levels were observed for cytokines IL-6, VEGF, and CCL-2. VILIP-a was revealed to differentiate most in principle component analysis. Cytokines with the lowest overall expression, such as TGF-β1, β-NGF, TNF-α, and TREM1, showed low intratumoral heterogeneity, in contrast to βNGF, TNF-α, and IL-18, which displayed high heterogeneity despite low expression. The study showed high intratumoral heterogeneity in GBM, emphasizing the need for a more detailed understanding of the tumor microenvironment. The described findings could be essential for future personalized treatment strategies and the implementation of reliable diagnostics in GBM.
Online veröffentlicht: 10. November 2024
Gesehen am 30.07.2025